Application of Newly Developed Activated Carbon Coated Chitosan in Cosmetics: An Innovative Research - Hunge S.S. (Chemical and Materials Sciences: Developments and Innovations Vol. 8, 2024)
Cosmetics are the products used to clean, beautify, increase attractiveness or change the appearance of the human body without affecting the structure or function of the body. Masks are treatments that are applied to the skin for a certain period of time and then removed. Use them to get a generally dry and clean face, avoiding the eyes and lips. Clay masks contain kaolin or bleach which carry essential oils and chemicals into the skin and are usually affected until completely dry. When the clay dries, it absorbs excess oil from the skin and can help unclog pores. Due to its drying effect, clay masks are only suitable for oily skin. Scanty references are available on the use of charcoal and activated carbon in cosmetics. Charcoal is known for its ability to absorb impurities. Face pack containing charcoal with kaolin clay or fuller's earth as its base absorbs/ adsorbs dirt and oil from the pores, leaving skin cleaner and healthier. In the present investigation, the use of chitosan impregnated with activated carbon derived from cotton stags in cosmetics (face masks) has been reported. The material has been proven to be a good dirt and oil adsorbent when applied with kaolin clay or fuller's earth-based face masks. This study therefore suggests that activated carbon-coated chitosan is suitable to be used with face packs for improved cosmetic applications.